Desordens temporomandibulares em usuários de prótese parcial removível: prevalência de acordo com a classificação de Kennedy - Jorge, Janaina Habib [UNESP] (2013)
OBJECTIVE: The aim of this study was to determine the prevalence of temporomandibular disorders in patients with removable partial dentures according to Kennedy classification. METHOD: The population consisted of patients who required care at the State University of Ponta Grossa. The patients wore complete upper and lower removable partial dentures between 1 to 5 years. The patients were divided into five groups (n = 15): G1: wearer of complete maxillary denture opposed by a Class I (Kennedy) removable partial denture; G2: wearer of complete maxillary denture opposed by a Class II (Kennedy) removable partial denture; G3: wearer of complete maxillary denture opposed by a Class III (Kennedy) removable partial denture; G4: wearer of complete maxillary denture opposed by a Class IV (Kennedy) removable partial denture and G5: fully dentate patients (control group). Fonseca's questionnaire was applied to verify the level of TMD. The qui-square test (α = .05) was used to analyze association between the variables. RESULT: No statistical difference (P > 0.05) was found among groups. All groups showed mild or moderate TMD. CONCLUSION: The findings from this clinical study showed that the presence of TMD in wearers of removable partial denture could not be correlated to the classification of Kennedy, since the presence of TMD for edentulous patients and dentate patients appeared similar.